Citizens’ satisfaction on the urban environmental quality - Lebedeva-Nesevria N.A.; Barg A.O. (E3S Web of Conferences, 2024)
The research goal was to estimate public satisfaction with ambient air quality in an industrial city in Russia and describe certain peculiarities in the perception of related health risks. The resulting estimates were used as grounds for describing urban environmental quality. The empirical base of the research was provided by the results of a social study performed in a Russian city with over a million inhabitants. That city was included into the “Clean air” Federal project. The data were collected by conducting an internet survey (n=544). Having analyzed these data, we detected that public satisfaction with ambient air quality was rather low (not more than 11% of the participants chose the variants “quite satisfied” or “fully satisfied”). Most respondents estimated ambient air quality as being “poor” or “very poor” (giving a 3-score estimate or even lower according to a 7-score scale). They also believed that air pollution produced negative effects on their health. People living in an industrial city tend to have alarmist perception of health risks. These risks seem uncontrollable and involuntary to them. Women are a more risk-sensitive group in comparison with men. These obtained data corroborate a hypothesis about a direct relationship between actual and perceived environmental pollution.